The Influence of Teacher Communication Quality with Learning Motivation in PJOK Subjects - Andhika Eka Wardhana; Muhammad Ramli Buhari; Hamdiana Hamdiana; Pariyadi Pariyadi (FKIP - Universitas Riau, 2026)
The effectiveness of teacher-student communication plays a crucial role in shaping students’ learning motivation and engagement. Physical Education, Sport, and Health (PJOK) provides a unique learning context because instructional activities involve both verbal and non-verbal communication and are often conducted in environments prone to distractions. Although previous studies have highlighted the importance of teacher communication in supporting learning motivation, limited evidence is available regarding this relationship in PJOK learning. Therefore, this study aimed to examine the relationship between teacher communication quality and students’ learning motivation in PJOK subjects at SMA Negeri 2 Tenggarong. A quantitative correlational approach was employed involving tenth-grade students selected through cluster sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using Spearman’s rank correlation with the assistance of IBM SPSS Statistics software. The findings revealed a significant positive relationship between teacher communication quality and students’ learning motivation, with a correlation coefficient of 0.744 and a significance value of 0.000. Teacher communication contributed 55.3% to the variance in students’ learning motivation, while the remaining 44.7% was influenced by other factors. These findings indicate that effective teacher communication can enhance students’ motivation, participation, and engagement in PJOK learning.